Development of Genially Based Interactive Learning Multimedia for Social Studies (IPS) in Grade VII at SMP Negeri 32 OKU - Aziza Sri Wahyuni; Yamanto Isa; Leni Pebriantika (Indonesian Technology and Education Journal, 2026)
This research is motivated by the limited use of technology-based learning media in Social Science subjects at SMP Negeri 32 OKU, where instruction still relies on conventional textbooks. The abstract nature of Social Science topics, specifically "Life in the Pre-literacy Era," often leads to low student motivation and difficulty in conceptualizing historical events. The primary objective of this study is to develop a website-based interactive learning multimedia using Genially and Canva platforms to create a more engaging and flexible learning environment. The research follows the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation) combined with Tessmer’s formative evaluation stages, including expert review, one-to-one, small group, and field testing. Results from expert validation show high feasibility scores: 92.4% from material experts, 86.1% from learning design experts, and 87.5% from media experts. In practical application, the field test involving 32 students yielded an average score of 89.8%, placing the product in the "Very Good" category. The conclusion of this research is that the developed website-based interactive multimedia is valid, practical, and effective for use in Social Science instruction. This product contributes a modern technological solution to enhance independent learning and student engagement in the digital era.